Artificial Neural Network Methods for the Solution of Second Order Boundary Value Problems - Anitescu, Cosmin; Atroshchenko, Elena; Alajlan, Naif; Rabczuk, Timon (Computers, materials & continua, 2019)
We present a method for solving partial differential equations using artificial neural networks and an adaptive collocation strategy. In this procedure, a coarse grid of training points is used at the initial training stages, while more points are added at later stages based on the value of the residual at a larger set of evaluation points. This method increases the robustness of the neural network approximation and can result in significant computational savings, particularly when the solution is non-smooth. Numerical results are presented for benchmark problems for scalar-valued PDEs, namely Poisson and Helmholtz equations, as well as for an inverse acoustics problem.